PROMOSI EKSPOR INDONESIA DALAM UPAYA PENINGKATAN EKSPOR KOPI KE AMERIKA SERIKAT PERIODE 2017-2020 - Muhammad Ivan Adriansyah (2022)
Coffee is the second largest traded commodity in the world after oil and gas, coffee as a product is widely enjoyed by all people in the world, including the demographics of the United States who import coffee from coffee-producing countries to meet their demands following the consumption trends of coffee in their country. Indonesia is one of the largest coffee producing country in the world After Brazil, Vietnam and Colombia, coffee is one of Indonesia's strategic export commodity which is exported to meet the demands of foreign markets such as the United States. The Indonesian coffee industry has good potential to compete in the United States market, but fact has shown a tendency to decline in export figures in the 2017-2020 period. This study will discuss the economic diplomacy pursued by Indonesia through its export promotion strategy to increase its coffee exports in the United States. The results of Indonesia's economic diplomacy show a positive impact, although it does not have a direct impact on export numbers. Indonesian coffee industry has to develop to meet the standards of international coffee market demands, and also have to increase the rate of coffee productions productivity in order to be able to compete with the other competitors. Economic diplomacy through export promotion is just one of many factors that could help boost Indonesian coffee export figures to the United States in the next period.